2020
DOI: 10.3390/pharmacy8030160
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Prescribing in Saudi Arabia: Cross-Sectional Study Describing Current Practices and Future Perspectives

Abstract: Pharmacist prescribing is being increasingly undertaken to better use their skills and reduce the workload of existing prescribers such as doctors, often using formal processes to legitimate these activities. In developing countries like Saudi Arabia, however, pharmacists’ prescribing remains informal with no legislation or formal training and there is a lack of research and understanding into such practices. Therefore, we aimed to describe current pharmacist prescribing practices in Saudi Arabia and explore p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In agreement with our findings, a previous study observed that about 53.0% of students judged patients’ pain poorly, and only 10% knew the suggested course of medialization for cancer patients. 34 This proves that the pharmacy practical education system in Saudi Arabia needs to improve its educational programs related to pain management at pharmacy colleges. An intensive program should be taught that prevents drug misuse, improves the medication safety system, prevents medication errors, improves patient outcomes and avoids unnecessary economic burdens on healthcare organizations.…”
Section: Discussionmentioning
confidence: 94%
“…In agreement with our findings, a previous study observed that about 53.0% of students judged patients’ pain poorly, and only 10% knew the suggested course of medialization for cancer patients. 34 This proves that the pharmacy practical education system in Saudi Arabia needs to improve its educational programs related to pain management at pharmacy colleges. An intensive program should be taught that prevents drug misuse, improves the medication safety system, prevents medication errors, improves patient outcomes and avoids unnecessary economic burdens on healthcare organizations.…”
Section: Discussionmentioning
confidence: 94%
“…They work under a collaborative agreement with doctors that permits pharmacists to prescribe medications and order laboratory tests as long as they adhere to the agreement’s terms and conditions. Presently, there is no national regulation that supports any official prescribing by pharmacists in Saudi Arabia, these actions are nonetheless regarded as informal forms of prescribing [ 40 ]. Zehnder et al stated that there is a demand for more websites tailored to pharmacists’ needs and suggested that pharmacists have to quickly adapt to the changes in drug information resources ahead to remain competitive [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The position of nurses involved in care involving provision of drugs needs to be clearly delineated in a codi ed and mandated manner to recognize this aspect of their clinical practice. Progress in this area may facilitate an increased recognition of the complicated requirements of providing this care, offer a more sensitive and pertinent strategy, potentially reward those who accept this responsibility, and assist in the establishment of robust multi-disciplinary teams constituting nurses, pharmacists, and physicians in mental health care services [3,21,[38][39][40][41][42][43][44].…”
Section: Trainingmentioning
confidence: 99%